Proteção social brasileira, amparo e desamparo aos povos indígenas - Cardoso, Cynthia Franceska (2012)
Until the 80 s, indigenous and social Brazilian policies walked side by side, without intersecting each other. After the promulgation of the Constitution of 1988 these policies were articulated in a fragmented and even residual way, directly influencing the daily life of indigenous inhabitants of the national territory. However, there were no predictions of the consequences in the lives of those people. The intent of this research was to analyze the influence of social policies in daily life of the Guarani Mbyá people, located in the Ribeira Valley, in the State of São Paulo, in seven villages in the municipalities of Iguape, Cananéia , Pariquera-Acu and Sete Barras. The methodology was based on Participatory Action Investigation (IAP), which proposes, among others, the active participation of the subjects involved in research aiming their social role as protagonists. The field research lasted eighteen months, which allowed an analysis of the effectiveness of the social protection policies related to Guarani Mbya people. The concept of social protection policies used throughout the paper refers to the following public policies: education, health, social welfare, retirement, food security, shelter / housing - land and environment, this last one included in the sphere of social policies, since the self-sustainability, culture, worldview, cosmology of that people are intrinsically linked to the environment. The analysis about the influence of social policy highlights the income transfer programs, which are mainly responsible for the current social protection, especially the program called Bolsa Família, the most used among all. To sum up, this represents the access to income transfer programs by indigenous people